2012
DOI: 10.1136/bmjqs-2012-000986
|View full text |Cite
|
Sign up to set email alerts
|

Unannounced in situ simulations: integrating training and clinical practice

Abstract: Simulation-based training for healthcare providers is well established as a viable, efficacious training tool, particularly for the training of non-technical team-working skills. These skills are known to be critical to effective teamwork, and important in the prevention of error and adverse events in hospitals. However, simulation suites are costly to develop and releasing staff to attend training is often difficult. These factors may restrict access to simulation training. We discuss our experiences of 'in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 21 publications
3
37
0
1
Order By: Relevance
“…An advantage of ISS is that it is conducted in the real workplace, thus making it possible to train staff and also identify systemic weaknesses, which in turn forms the basis for required organisational changes 15–18. Some have argued that ISS is more feasible and cost saving compared with traditional simulation conducted in simulation centres 19 20. Some studies concluded that ISS is met with widespread acceptance among participants and has resulted in a collaborative approach to patient safety 14 19 21 22…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of ISS is that it is conducted in the real workplace, thus making it possible to train staff and also identify systemic weaknesses, which in turn forms the basis for required organisational changes 15–18. Some have argued that ISS is more feasible and cost saving compared with traditional simulation conducted in simulation centres 19 20. Some studies concluded that ISS is met with widespread acceptance among participants and has resulted in a collaborative approach to patient safety 14 19 21 22…”
Section: Introductionmentioning
confidence: 99%
“…3 The results of this CEP led us to believe that overall performance of the staff could be improved if staff members were trained in situ and over a short period because each member would acquire the same background and follow the same algorithm. Although several studies have shown that in situ simulation training improves the individual skills of professionals 4,5 and the quality of care, [6][7][8][9][10] to our knowledge, there are no data regarding the impact of in situ training on global performance in neonatal resuscitation .…”
mentioning
confidence: 99%
“…As InST happens in actual clinical environments, approval of the senior clinical and management teams in paediatric A&E and NNU was obtained by presenting the evidence supporting the role of InST in detecting LSTs1 2 and improving multidisciplinary team working 1–3. The local National Health Service trust's postgraduate education department fully supported the simulation training programme.…”
Section: Making a Case For Changementioning
confidence: 99%